Size Of Savings And Its Impact On Private Investment In The Iraqi Economy For The Period (2004-2023): An Econometric Study - Marwa Allawi Naji (Indonesian Journal Publisher, 2026)
The research was based on identifying the theoretical and conceptual framework for both saving and private investment, in addition to analyzing and measuring the reality and impact of saving on private investment in Iraq during the period (2004-2023)، Given the importance of these two variables from an economic perspective, the research aimed to identify some economic variables represented by savings and private investment, as well as to analyze the reality of changes in savings and private investment in Iraq during the period (2004-2023)، Also, the study addressed the standard aspect to determine the size of the impact that savings can have on private investment during the research period in Iraq. The ARDL distributed interval model was used based on the stability results, where both savings and private investment were stable at the specified level، Furthermore, there is long-term cointegration between them, in addition to the absence of an autocorrelation problem. Accordingly, the null hypothesis was accepted and the alternative hypothesis was rejected because the probability values ​​were greater than 0.05. Then, a set of results and suggestions were reached, the most important of which was raising awareness among individuals and encouraging them to reduce their level of consumption and increase their savings so that they can grow their investments،the research also recommended the need to provide government support to the private sector by increasing bank financing, which in turn would increase the volume of private investment.